Design and Development of Bi-layered Sustained Release Azithromycin Tablets - Islam, Muhammad Rashedul; Moghal, Md Mizanur Rahman; Bari, FM Shah Noman Ul; Mamun, Elias Al (Dhaka University Journal of Pharmaceutical Sciences, 2017)
The objective of the current study was to develop a bilayer tablet of Azithromycin containing both immediate and sustained layer and evaluate the effect of formulation variables on drug release. Thirty different formulations (F-1 to F-30) were prepared by direct compression. When the fraction of polymer was increased from 5.55% to 10%, the rate of drug release was found to be slower. Maximum release of Azithromycin was from F-11 (within 8 hours), which contained 50 mg (5.55%) of HPMC 50 cps. Slowest release was observed from F-30 containing 90 mg (10%) of Carbopol 974 P. The IR spectral analysis revealed that all rate regarding agents and excipients used in this study are compatible with the active Azithromycin. Dhaka Univ. J. Pharm. Sci. 15(2): 227-234, 2016 (December)